2012
DOI: 10.1002/adhm.201100040
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy in The Design of Micellar Shape for Cancer Therapy

Abstract: For cancer therapy, optimization of carrier features is necessary to effectively deliver the targeting agents to tumor sites. Biodegradable poly(ether-anhydrides) micelles with filamentous, rod-like, and spherical shapes are fabricated. Their size and morphology are characterized by AFM and TEM. The encapsulation of doxorubicin hydrochloride (DOX) into the micelles does not impact their shape. The effect of micellar shape on the drug loading capacity and encapsulation efficiency, as well as in vitro drug relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…A number of researchers focused on studying the effects of size, shape, protein corona, and surface properties on the uptake of Au NPs . Chithrani et al had observed that the cellular uptake of citric acid ligand‐modified Au nanospheres strongly depended on the size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers focused on studying the effects of size, shape, protein corona, and surface properties on the uptake of Au NPs . Chithrani et al had observed that the cellular uptake of citric acid ligand‐modified Au nanospheres strongly depended on the size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of these endocytosis mechanisms can help us to develop drug delivery carriers with better targeting specificity, higher cellular uptake efficiency, and better bioavailability. Nevertheless, for nanocarriers there are so many factors that can influence the endocytosis pathways, such as particle size,21, 22 morphology,22–25 surface charge,22, 26 and so on. Among these factors, the ratio of hydrophilic and hydrophobic moieties of copolymers as drug carriers cannot be ignored either.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the Cur‐Ms solution were transferred into dialysis bag (MWCO: 1000) with DI water to remove the unloaded Curcumin before freeze‐drying. Drug loading content (LC) and encapsulation efficiency (EE) were measured with UV‐vis spectrophotometer (UV‐2550, Shimadzu, Japan) and calculated as previous report …”
Section: Methodsmentioning
confidence: 99%